Determinants of personality and risky road behaviors at work in drivers of medical transport vehicles in the Wielkopolska (Greater Poland) Voivodeship - Marcin Cybulski; Wojciech Strzelecki; Maria Grzymisławska-Cybulska; Maria Danuta Głowacka; Ewa Mojs (Nofer Institute of Occupational Medicine, 2014)
Background: Personality determinants are an important predicator of road behaviors in drivers. The main objective of the study was to determine the relationship between personality determinants (neuroticism, extraversion, level of anxiety - features) and distinguishable risky behaviors of drivers of medical transport vehicles. Material and Methods: The study covered 106 male drivers from the Wielkopolskie Voivodeship, working in health care, having a license to drive emergency vehicles. To achieve the research objectives a questionnaire was developed and applied. It concerned risky road behaviors among drivers of medical transport. The personality suitability was determined using the questionnaire methods on self-assessment: Polish versions of Eysenck Personality Questionnaire - Revised (EPQ-R) and the State-Trait Anxiety Inventory (STAI) questionnaire. Results: It was shown that drivers with introverted characteristics declare driving vehicles of reduced technical efficiency more often than extroverts. The level of the anxiety as a trait A-characteristic affects the display of distracting behaviors, making decisions about driving a vehicle that is inefficient, driving in a bad psychophysical condition, as well as maintaining too small distance from the preceding vehicle. The higher the intensity of anxiety characteristics, the higher the intensity of given behaviors. Conclusions: Based on the study results, it can be assumed that there is a relationship between determinants of personality and the display of risky behaviors of drivers of medical transport vehicles. Thus it can be concluded that the level of extraversion and anxiety as a trait are the differentiating characteristics of respondents. Med Pr 2014;65(4):485-496